Aceclofenac Derivatives: Synthesis, Characterization, and Determination of Anti‐oxidant and Anti‐inflammatory Activities by Chemiluminescence Assays and Molecular Docking Studies. Issue 11 (14th March 2023) - Raza, Asim; Abbas Khan, Mohsin; Ahmad, Irshad; Bari, Ahmad; Masood, Anum; Ullah, Farhat; Awan, Breena
Abstract: Aceclofenac (ACF) is a newer derivative of diclofenac, and one of the emerging NSAIDs for the treatment of various inflammatory diseases. In this research we have develop a set of 2‐(2‐(2‐((2, 6‐dichlorophenyl)amino)phenyl)acetoxy)acetic acid derivatives (AR1‐AR12) using Fischer esterification in good yields and in an efficient manner. All the compounds were fully characterized physical (solubility and melting points) and chemical by spectral data analysis of FTIR, 1 HNMR and 13 CNMR and elemental analysis. In‐vitro anti‐inflammatory activity was performed by Chemiluminescence technique in which we found 2‐oxo‐1, 2‐diphenylethyl2‐(2‐(2((2, 6‐dichlorophenyl)amino)phenyl) acetoxy)acetate (AR2 71 % ), 2‐(4‐formyl‐2‐methoxyphenoxy)‐2‐oxoethyl2‐(2‐((2, 6 dichloro‐phenyl) amino)phenyl)acetate (AR3 74.7 % ), 2‐(2‐(2‐(2‐((2, 6‐dichloropheny l)amino) phenyl) acetoxy) acetoxy)‐3‐(2‐(2‐(3‐((2, 6‐dichlorophenyl) amino) phenyl) acetoxy)acetoxy)succinic acid (AR6 89.2 % ), 2‐(4‐aminophenoxy)‐2‐oxoethyl2‐(2‐((2, 6‐dichloro‐phenyl) amino) phenyl) acetate (AR8 71.1 % ), 1, 3‐dioxo‐2, 3‐dihydro‐1H‐indene‐2, 2‐diyl bis(2‐(2‐(2‐((2, 6‐dichlorophenyl)amino)phenyl)acetoxy)acetate) (AR9 76.3 % ) found more potent as compared to parent compound while AR3, AR6 and AR9 highly potent than standard reference ibuprofen (73.2 % ). The current molecular docking study was performed In order to check the suitable method for the binding of target ligands and proteins Glide docking with extra precision (XP) mode. The hydrogen bonding interactions of Aceclofenac are prominent with Isoleucine moiety, those of compound AR‐6 shows hydrophobic interaction with active amino acid Leucine and Phenylalanine moieties. Anti‐oxidant activities were also performed, AR‐3 (79.30 % ), AR‐5 (91.23 % ), AR‐9 (83.43 %) AR‐12 (92.43 % ) were found to be more anti‐oxidant as compared to aceclofenac (ACF) (66.46 % ). These derivatives were synthesized with different aliphatic and aromatic alcohols and phenols. Abstract : A series of aceclofenac ester derivatives were synthesized and evaluated as their invitro anti‐inflammatory activity as well as anti‐oxidant activity by various techniques. Among the synthesized derivatives AR6, AR3 and AR9 exhibit enhanced Anti‐inflammatory activity as compared to other synthesized compounds and parent drug. All derivatives of aceclofenac showed anti‐LOX activity in the active pocket. AR‐6 is most active compound like in LOX studies and also in COX studies.